2018
DOI: 10.1002/slct.201800757
|View full text |Cite
|
Sign up to set email alerts
|

An Aggregate Cluster‐Dispersed Electrolyte Guides the Uniform Nucleation and Growth of Lithium at Lithium Metal Anodes

Abstract: Rechargeable lithium metal battery technology is widely recognized as being a suitable candidate for replacing lithium ion batteries. A critical barrier preventing its application to electrical storage systems is that lithium grows irregularly, which is the fundamental cause of poor characteristics during a battery‘s lifetime, and also causes safety concerns. There are two reasons for the irregular growth of lithium: lithium prefers to nucleate on specific surfaces; subsequently, the lithium atoms grow rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It was thought that ether-based electrolytes were incompatible with high-voltage (>4 V vs Li + /Li) cathodes due to poor stability against oxidation . The surprising discovery of high oxidation stability (4.5 V vs Li + /Li) of equimolar LiTFSI–triglyme or LiTFSI–tetraglyme opened up opportunities for new electrolyte designs for high-voltage LMBs. , More recently, various ether-based low-concentration electrolytes, high-concentration electrolytes (HCEs), and localized high-concentration electrolytes (LHCEs) were developed. The combination of lithium bis­(fluoro­sulfonyl)­imide (LiFSI) and 1,2-dimethoxy­ethane (DME) was one of the most common electrolytes due to commercial availability, high salt solubility, good Li CE, dendrite suppression, and high ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…It was thought that ether-based electrolytes were incompatible with high-voltage (>4 V vs Li + /Li) cathodes due to poor stability against oxidation . The surprising discovery of high oxidation stability (4.5 V vs Li + /Li) of equimolar LiTFSI–triglyme or LiTFSI–tetraglyme opened up opportunities for new electrolyte designs for high-voltage LMBs. , More recently, various ether-based low-concentration electrolytes, high-concentration electrolytes (HCEs), and localized high-concentration electrolytes (LHCEs) were developed. The combination of lithium bis­(fluoro­sulfonyl)­imide (LiFSI) and 1,2-dimethoxy­ethane (DME) was one of the most common electrolytes due to commercial availability, high salt solubility, good Li CE, dendrite suppression, and high ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…22 Similar concepts have also been used by several other groups to improve the performance of LMBs and LIBs. 21,[35][36][37] Here, we give a brief review on the LHCEs we developed recently that are highly stable with both LMAs and high-voltage cathodes such as Ni-rich LiNi x Co y Mn 1-x-y O 2 (NMC) (x ⩾ 0.6) and LiCoO 2 . These LHCEs exhibit not just the advantages of highly concentrated electrolytes, but also low viscosity, and low cost of the low-concentration electrolytes.…”
mentioning
confidence: 99%
“…Herein, we introduce a new generation of LHCEs tailored for Si anodes using 1 H ,1 H ,5 H -octafluoropentyl 1,1,2,2-tetrafluoroethyl ether (OTE) as a diluent, which has a high boiling point of 133 °C. While several studies of OTE as a promising solvent have been reported for improving the cycling stability of Li–S, , Li–metal, and Li–air batteries, further investigation of utilizing OTE as a diluent is necessary for intercalation and alloying type anodes, such as graphite and Si. Electrolyte properties such as salt concentration and solvent-to-diluent ratio were tuned for optimized electrolyte physicochemical properties, ion coordination structure, and electrochemical performance.…”
mentioning
confidence: 99%